Water nutrient analysis and bacteriological assessment of milkfish (Chanos chanos) and mussel-oyster aquaculture sites in Leyte Gulf. - Asilo, Hannah Alexis M. (Hannah Alexis M. Asilo, 2019)
The water quality on the selected aquaculture sites of Leyte Gulf (Brgy. Kataisan in Tacloban City, Brgy. Guindapunan in Palo, Leyte, Brgy. Liberty in Mayorga Leyte, Brgy. San Roque in Marabut Samar, and Brgy. Trinidad in Guiuan Eastern Samar) were determined by measuring the physicochemical parameters in situ, as well as by performing bacteriological assessment and nutrient analysis on the water samples that were collected from three representative points of the aquaculture site. Nutrient levels were determined using spectrophotometric method. The fecal coliform and total coliform bacteria were assessed using membrane filtration method. Using one-way sample T-test, the differences between the standard values and the experimental results were measured to be significantly outside the standard range for temperature in Brgy. Kataisan and Brgy. Guindapunan, salinity in all sites except Brgy. Trinidad, DO levels in Brgy. Guindapunan and Brgy. San Roque, nitrite concentration and total coliform bacteria level in Brgy. Guindapunan, and fecal coliform bacteria level in Brgy. San Roque, suggesting that the levels of these parameters may provide an unfavorable environment for the aquacultures.